PENGGUNAAN METODE GUESS WORD UNTUK MENINGKATKAN HASIL BELAJAR SISWA: MI AL-FALAH KAJAR TENGGARANG BONDOWOSO - ANSORI ANSORI (Mitra Pendidikan, 2021)
The purpose of this study was to determine the success rate of student learning outcomes using the Guess Word method for class 3 MI Al-Falah Kajar Tenggarang Bondowoso for the 2019/2020 academic year. This type of research is Classroom Action Research (CAR) which aims to improve the quality of learning and improve student learning outcomes. The independent variable is the Guess Word method (guess the word) while the dependent variable is to increase students' learning motivation. This research was carried out in two cycles each cycle through four stages, namely; (1) planning, (2) action, (3) observation, (4) reflection. Data collection techniques using; (1) a test carried out at the end of each cycle. (2) observation or observation, is used to determine the learning activities of students in learning activities, and the implementation of learning scenarios by the teacher. Data were obtained during teaching and learning activities. (3) questionnaire. The results of the learning achievement test in cycle 2 showed 23 students completed, and 3 students did not complete with a percentage of completeness reaching 88%. When compared with learning completeness in cycle 1 which reached 69% in cycle 2, there was an increase in mastery of 19%. Thus, it can be concluded that the increase in student learning activities in thematic learning using the Guess Word method has an impact on increasing learning outcomes.